2012
DOI: 10.5539/jas.v4n2p275
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Myo-Inositol and Thiamine on Micropropagation of GF677 (Peach × Almond Hybrid)

Abstract: GF677 is a vigorous rootstock, used for both peach and almond worldwide. Nowadays, it is propagated is mainly through micro propagation. Widening and undesirable growth of leaves as well as poor rooting are major problems during its in vitro culture. In this study, effects of myo-inositol at 10 and 100 mg/l In MS medium were studied at explants establishment and shoot growth stages. Thiamine was also used in LS medium at 0, 1.6, 2.8 and 4 mg/l at rooting stage. This experiment was conducted in Randomized Compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
(6 reference statements)
2
3
1
Order By: Relevance
“…Our results were in accordance with the findings of Hepaksoy and Tanrisever (2004) on sweet cherry, Ruzic and Vujovic (2007) and Dolgov et al (2010) on Prunus domestica that all indicated that the highest shooting rate was obtained in the combination of BAP and IBA treatment. The present study findings are in opposite of Sepahvand et al (2011) on GF677 vegetative rootstock since they introduced BAP and NAA combination as the most appropriate compound for shooting. Here, the combination of BAP and IBA was the most effective treatment which is in accordance with other researchers’ findings conveyed that the effective shooting depends on the cytokinin type and concentration as well as suitable concentrations of cytokinin–auxin, i.e., using BAP along with low amounts of IBA is favorable for shooting ( Sedlák and Paprstein, 2007 ; Ruzic and Vujovic, 2008 ).…”
Section: Discussioncontrasting
confidence: 82%
“…Our results were in accordance with the findings of Hepaksoy and Tanrisever (2004) on sweet cherry, Ruzic and Vujovic (2007) and Dolgov et al (2010) on Prunus domestica that all indicated that the highest shooting rate was obtained in the combination of BAP and IBA treatment. The present study findings are in opposite of Sepahvand et al (2011) on GF677 vegetative rootstock since they introduced BAP and NAA combination as the most appropriate compound for shooting. Here, the combination of BAP and IBA was the most effective treatment which is in accordance with other researchers’ findings conveyed that the effective shooting depends on the cytokinin type and concentration as well as suitable concentrations of cytokinin–auxin, i.e., using BAP along with low amounts of IBA is favorable for shooting ( Sedlák and Paprstein, 2007 ; Ruzic and Vujovic, 2008 ).…”
Section: Discussioncontrasting
confidence: 82%
“…Our results showed that the increase in myo-inositol concentration inhibits the shoot length of both rootstocks which is in agreement with the results by Sepahvand et al (2012) using the peach rootstock GF-677. However, Al-Sulaiman (2010) found no significant effects of myoinositol on the shoot length of Ziziphus spina-christi.…”
Section: Rootstocksupporting
confidence: 92%
“…Based on our results, it is possible that IBA positively interacts with the two vitamins promoting AR-elongation as the necessary premise for ARbranching. In accordance, a positive thiamine and IBA interaction in favouring AR-elongation has been demonstrated in the micropropagation of GF677 (peach × almond hybrid) (Sepahvand et al 2012). Moreover, AR-elongation was also favoured by specific combinations of IBA and myo-inositol in cherry rootstocks CAB-6P and Gisela 6 (Sarropoulou et al 2013).…”
Section: Myo-inositol and Thiamine Cooperate With Exogenous Iba In Ensupporting
confidence: 68%
“…Synergistic interactions between thiamine and auxins have been reported for different plant rooting systems, as Jatropha curcas and Tectona grandis cuttings (Dhillon et al 2011, and references therein), and GF677 (peach x almond hybrid) shoot microcuttings. In the latter, significant rooting increments were detected at different IBA levels, but always when thiamine was present even at low levels (Sepahvand et al 2012). Thiamine may also interact positively with cytokinins.…”
Section: Introductionmentioning
confidence: 93%